Effect of Tapuy (Philippine Rice Wine) Lees on the Gut Microbiota Profile and Lifespan under Normal and Stress Conditions in Drosophila melanogaster - Ma Carmela P. Dela Cruz; Paul Mark B. Medina (Biomedical and Biotechnology Research Journal)
Background: Tapuy lees are by-products generated during rice wine fermentation in the northern region of the Philippines. These lees have been reported to contain high concentrations of proteins and dietary fibers. However, studies showing the potential biological effects of consuming these lees are currently lacking. Thus, despite occasional local consumption, most Tapuy lees are discarded after rice wine production. To address this, the current study investigated the potential health effects of Tapuy lees consumption using Drosophila melanogaster as model. Methods: The effects of four Tapuy lees variants on the gut microbiome composition and lifespan under normal, heat stress, and starvation stress conditions were tested in D. melanogaster compared to a media-only negative control and the prebiotic inulin as positive control. Results: All tested Tapuy lees variants increased the abundance of probiotic gut bacteria in both male and female flies, comparable to the effect of the commercial prebiotic inulin. Moreover, Tapuy lees extended the lifespan of both male and female D. melanogaster under normal, heat stress, and starvation stress conditions. Conclusions: All in all, our results demonstrate the beneficial effects of Tapuy lees on the lifespan and gut microbiota composition in D. melanogaster. These findings suggest that Tapuy lees could be considered functional food products. Further studies are recommended to evaluate their potential benefits for human health.